2009
DOI: 10.1175/2009jhm1089.1
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Winter/Spring Snowfall and Summer Precipitation in the Northern Great Plains of North America

Abstract: On the basis of snowfall observations from 1929 to 1999, positive (negative) snowfall anomalies are associated with wetter (drier) than normal conditions during the summer [July-August (JJA)] in the northern Great Plains. The five driest summers are associated with negative snowfall anomalies during the preceding winter (266.7 mm) and spring (262.4 mm) that cover most of the study region (;85%). Snowfall anomalies during the late spring (April-May) are more important for determining summer moisture conditions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 78 publications
(84 reference statements)
2
11
0
1
Order By: Relevance
“…Our results show positive correlation between the SPI and soil moisture, which are in line with the results reported by Quiring and Kluver () and Wu and Kinter () attesting the appropriateness of SPI to assess the soil moisture. Several studies dealing with drought–soil moisture relationship (Sims and Raman, ; Dai et al , ) demonstrate that the strongest correlation between PDSI and soil moisture is shown in late summer, and the weakest correlation is shown in spring, when snowmelt is an important contributor to soil moisture.…”
Section: Discussionsupporting
confidence: 93%
“…Our results show positive correlation between the SPI and soil moisture, which are in line with the results reported by Quiring and Kluver () and Wu and Kinter () attesting the appropriateness of SPI to assess the soil moisture. Several studies dealing with drought–soil moisture relationship (Sims and Raman, ; Dai et al , ) demonstrate that the strongest correlation between PDSI and soil moisture is shown in late summer, and the weakest correlation is shown in spring, when snowmelt is an important contributor to soil moisture.…”
Section: Discussionsupporting
confidence: 93%
“…A negative relationship was found between the winter PNA index and FHB intensity in Ohio at a period of 5.1 years, and between the spring PNA index and FHB intensity in Indiana for several periods. Ge et al (19) showed that the PNA is associated with snow pack in several parts of the United States, and recent work (13,41) has begun to investigate the effect of winter/ spring snow mass anomalies on the spring/summer season. Coleman and Rogers (6) showed that the PNA index was inversely related to winter precipitation in the Ohio River Valley region, with the strongest relationship found in southern Indiana.…”
Section: Discussionmentioning
confidence: 99%
“…However, the effects of snowfall/snowmelt on recharge were not as significant as extreme rainfall in other seasons in this study region. In addition, the relationship between winter/spring snowfall and summer soil moisture was partly explained by soil moisture in the Northern Great Plains (Quiring and Kluver, 2009). …”
Section: Dynamics Of Gwr and Epmentioning
confidence: 99%